Implementasi Manajemen Bimbingan Konseling Kelompok di SMA Negeri 1 Cikalong - Elsa Nuraidah; Eran Wandani; Husni Mubarok; Neni Eliawati (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2024)
The implementation of guidance and counseling in educational institutions requires well-systemized management of guidance and counseling by the parties providing guidance and counseling in schools. This research aims to determine the implementation of guidance group management, its implementation, and the need for the availability of guidance group management. This research used a qualitative approach and was conducted at SMA Negeri 1 Cikalong. Data collection techniques include interviews and documentation, while data analysis uses data reduction, presentation and drawing conclusions. The results of the research show that efforts to implement implementation at SMA Negeri 1 Cikalong emphasize active student participation in the group counseling guidance process. The program for implementing group counseling guidance at SMA Negeri 1 Cikalong has a mature framework to ensure success and relevance in providing group counseling guidance services. One of the important elements in this program is the implementation of assessments and the use of questionnaires as evaluation instruments. By involving students directly, this program creates an environment that supports the exchange of experiences and ideas between peers.